EVALUATION OF THE QUALITY OF PROGRAM AND ACTIVITY PLANNING AT THE SOCIAL AFFAIRS OFFICE OF MALUKU PROVINCE: A DATA-BASED PARTICIPATORY PLANNING PERSPECTIVE - Alfa Maximille Tutuhatunewa; Wahab Tuanaya; Hendry Selanno (SOSIOEDUKASI, 2026)
This study examines the quality of program and activity planning at the Social Affairs Office of Maluku Province from a data-based participatory planning perspective. High-quality planning is essential for ensuring that social welfare programs are effective, efficient, and responsive to real community needs, particularly in a geographically dispersed and socially diverse region such as Maluku. Using a qualitative research approach, data were collected through in-depth interviews, direct observation, and document analysis involving key planning actors within the institution. The findings indicate that planning practices have increasingly incorporated stakeholder participation and the use of social data to identify priority issues and design targeted interventions for vulnerable groups. Participatory mechanisms involving government units, community representatives, and traditional leaders contribute to greater contextual relevance and policy alignment. In addition, the utilization of integrated social data supports more evidence-based decision-making and program justification. However, the study also reveals several challenges, including limited depth of stakeholder involvement in decision-making, inconsistencies in data quality and integration, uneven analytical capacity among planners, and weak feedback follow-up mechanisms. These constraints limit the full realization of participatory and data-driven planning as a strategic tool for social development. The study concludes that strengthening institutional capacity, improving data governance, and enhancing inclusive participation are critical to improving planning quality and ensuring sustainable social welfare outcomes in Maluku Province.